2013
DOI: 10.1186/1477-7517-10-15
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of an intensive case management program for injection drug users on antiretroviral therapy in St. Petersburg, Russia

Abstract: BackgroundThe majority of HIV-infected individuals requiring antiretroviral therapy (ART) in Russia are Injection Drug Users (IDU). Substitution therapy used as part of a comprehensive harm reduction program is unavailable in Russia. Past data shows that only 16% of IDU receiving substance abuse treatment completed the course without relapse, and only 40% of IDU on ART remained on treatment at 6 months. Our goal was to determine if it was feasible to improve these historic outcomes by adding intensive case man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Consequently, this has also led to improvements in clinical results. Specifically, in this study, the results of the multivariate logistic regression analysis indicated that patients who received the new case management model were at decreased odds of developing virological failure ( P < 0.001), which is consistent with other findings [ 32 – 34 ]. More so, those receiving case management experienced consistently higher survival rates compared to those in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, this has also led to improvements in clinical results. Specifically, in this study, the results of the multivariate logistic regression analysis indicated that patients who received the new case management model were at decreased odds of developing virological failure ( P < 0.001), which is consistent with other findings [ 32 – 34 ]. More so, those receiving case management experienced consistently higher survival rates compared to those in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…There were 10 studies that did not control for confounders in their analysis of follow-up adherence among ART participants (20–22, 24–29). While there was clearly bias introduced among included primary studies, we did not note any systematic bias that would lead to removal from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Case management and patient navigation can connect separated health care systems (Mugavero, Norton, & Saag, 2011; Pecoraro et al, 2015) and facilitate engagement with HIV care (Bradford, Coleman, & Cunningham, 2007; Gardner et al, 2005). Such an approach was shown promising in pilot research from Russia (Shaboltas et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that facilitators of HIV care include case management, psychological and social support, opioid agonist therapy, integrated addiction and HIV treatment, acceptance of HIV status, and addressing HIV and drug stigma (Kamarulzaman & Altice, 2015; J. D. Kelly, Hartman, Graham, Kallen, & Giordano, 2014; Samet et al, 1995; Shaboltas et al, 2013). However, this prior work is largely quantitative and not specific to PWID, providing limited insight into how these factors affect care utilization among PWID.…”
Section: Introductionmentioning
confidence: 99%